Tšeptsa jõgi põhjaudmurtide rahvakultuuris - Nadezhda Shutova (Mäetagused)
The Cheptsa River has played a significant economic and social role in the history and culture of the Northern Udmurts since the ancient times. There were hunting grounds, pastures and hayfields on the river’s floodplain. The river is a source of drinking and technical (industrial) water, as well as protein products. It serves as a means of a cultural, political and commercial communication. The river is an important mythological symbol, and also an element of sacred topography. The purpose of the paper is to define the role and significance of the Cheptsa River in the traditional religious and mythological worldview of the Udmurts. The research materials include the author’s field data from the late 20th – early 21st centuries, archaeological, folklore and ethnographic literature of the late 19th – early 20th centuries, and the late 20th – early 21st centuries. For the first time, the role of the Cheptsa River in the formation of the ethno-territorial community of the Northern Udmurts is analysed. It is revealed that the river valley is understood and perceived as a common ethnic, family and tribal territory. It is shown that the Cheptsa River performs not only economic and cultural, but also metaphysical, irrational functions in the life of the Northern Udmurts. The semantics of the Cheptsa River is characterized as a symbol of the homeland, a road in real and mythological dimensions, a border between worlds, a means of getting rid of diseases, as a sacred value of local Udmurts. General cultural (stadial-typological) and original (specific) features in the veneration of the river are revealed. Peculiarities of the Northern Udmurts’ worldview are the ideas about the creatures of the aqutic world, the presence of a whole system of rituals and special places associated with the cult of the owners of the water element. It is argued that the anthropomorphic image of the water sphere masters occupied a more significant position in the Udmurt beliefs. Archaic female personifications of these river spirits and other images of water creatures have faded into the background. The author concludes that the Cheptsa River was an important economic, landscape, cultural and mythological object for the Northern Udmurts of the late 19th – early 20th centuries.